Orthopaedic Applications for PLA-PGA Biodegradable Polymers - Athanasiou, K. A.; Agrawal, C. M.; Barber, F. A.; Burkhart, S. S.
Biodegradable polymers, especially those belonging to the family of polylactic acid (PLA)and polyglycolic acid (PGA), play an increasingly important role in orthopaedics. These polymers degrade by hydrolysis and enzymatic activity and have a range of mechanical and physical properties that can be engineered appropriately to suit a particular application. Their degradation characteristics depend on several parameters including their molecular structure, crystallinity, and copolymer ratio. These biomaterials are also rapidly gaining recognition in the fledging field of tissue engineering because they can be fashioned into porous scaffolds or carriers of cells, extracellular matrix components, and bioactive agents. Although their future appears to be bright, several questions regarding the biocompatibility of these materials linger and should be addressed before their wide-scale use. In the context of musculoskeletal tissue, this report provides a comprehensive review of properties and applications of biodegradable PLA/PGA polymers and their copolymers. Of special interest are orthopaedic applications, biocompatibility studies, and issues of sterilization and storage of these versatile biomaterials. Also discussed is the fact that terms such as PLA, PGA, or PLA-PGA do not denote one material, but rather a large family of materials that have a wide range of differing bioengineering properties and concomitant biological responses. An analysis of some misconceptions, problems, and potential solutions is also provided.
Keywords: BIODEGRADABLE; BIOABSORBABLE; POLYMERS; POLYLACTIC ACID; POLYGLYCOLIC ACID